Precipitated calcium oxide nanosize from limestone and blood clam shells - Caecilia - Pujiastuti; Srie Muljani; Ketut Sumada (Journal of Natural Sciences and Mathematics Research, 2023)
Calcium oxide (CaO) is a product that is needed by various types of industries such as the pharmaceutical, chemical, agricultural and health industries. CaO is generally produced by the calcination method of CaCO3 materials such as calcium carbonate rocks or from various types of shells. The calcination method requires a large amount of energy because the operating temperature is above 1000 C and the resulting calcium oxide product is still micrometer size. This study developed nanosize precipitated CaO from two calcium sources, namely blood clam shells and limestone. For clam shells using hydrochloric acid as a solvent and sodium hydroxide as a precipitating agent, while for limestone using phosphoric acid as a solvent and potassium hydroxide as a precipitating agent. The effect of acidity (pH) and calcination temperature on the characteristics of the precipitated CaO was observed. The blood calm shell produces precipitated CaO 85-92 % with a particle size of 200-250 Nm and the limestone produces precipitated CaO 42-66% with a particle size of 250-300 NmÂ